(untitled) (GEOmedia, 2022)
This work shows the processing of additional information using high and medium-resolution multispectral satellite images. The new information obtained from specific spectral indices will converge with the data obtained from official sources in a single database, thus constituting a real parametric model of the city under study. An extended model of urban planning called “CIM” (City Information Modeling) will be developed, to which it is possible to associate information of different nature, which helps to monitor and manage the city.